A new species of Opisthopatus Purcell, 1899 (Onychophora: Peripatopsidae) from KwaZulu-Natal, South Africa - Ruhberg, Hilke; Hamer, Michelle L. (Zootaxa, 2005)
The South African Peripatopsidae comprise two genera: Peripatopsis Pocock, 1894 (eight described species) and Opisthopatus Purcell, 1899 (two described species, and three subspecies currently debated). Recent collecting in South Africa produced a new and unusual onychophoran, Opisthopatus herbertorum sp. nov., from Mt. Currie Nature Reserve, KwaZulu-Natal. The new species is characterised by 17 pairs of legs, 15 complete dorsal plical folds per body segment, a lack of body-pigmentation, and reduced eyes. A key to the three species of Opisthopatus is provided. Other species of white onychophorans have been identified in South Africa, Australia and Jamaica; some of these species are cave-dwellers. The discovery of O. herbertorum sp. nov. from a small, isolated forest patch means that this species may be threatened with extinction, mainly through fire or other stochastic events. The habitat contains species of myriapods typical of forests, which suggests that the fauna is relictual, and that small forest patches have high conservation value. The discovery of the new species also highlights the lack of knowledge about forest invertebrates in South Africa, and raises the possibility of a far greater onychophoran diversity in the country.